2017
DOI: 10.15678/znuek.2017.0961.0108
|View full text |Cite
|
Sign up to set email alerts
|

Rolnictwo ekologiczne i perspektywy jego rozwoju w Polsce w świetle doświadczeń unijnych

Abstract: Celem artykułu jest analiza potencjału i tendencji rozwoju rolnictwa ekologicznego w wybranych krajach Unii Europejskiej, a także ocena szans i możliwości rozwoju tej formy rolnictwa w Polsce. Rolnictwo ekologiczne stanowi obecnie jedną z najszybciej rozwijających się gałęzi rolnictwa w Unii Europejskiej. W Polsce rynek produktów ekologicznych znajduje się na początkowym etapie rozwoju. Bariery rozwoju związane są z obszarem zarówno podaży, jak i popytu na produkty ekologiczne. Popyt na produkty ekologiczne ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
6
0
4
Order By: Relevance
“…However, it should be noticed that the differences between the two groups have somewhat diminished during the analyzed period, which may result, among other things, from a higher level of aid resources for organic farms. Also, (Ligenzowska, 2014;Duda-Krynicka and Jaskólecki, 2010;Golik and Żmija, 2017) indicated that this situation may result from the state policy regarding subsidies for organic production, because since Poland's accession to the European Union some aid resources strictly dedicated to organic agriculture have been implemented. Furthermore, in other EU countries, e.g.…”
Section: Production Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noticed that the differences between the two groups have somewhat diminished during the analyzed period, which may result, among other things, from a higher level of aid resources for organic farms. Also, (Ligenzowska, 2014;Duda-Krynicka and Jaskólecki, 2010;Golik and Żmija, 2017) indicated that this situation may result from the state policy regarding subsidies for organic production, because since Poland's accession to the European Union some aid resources strictly dedicated to organic agriculture have been implemented. Furthermore, in other EU countries, e.g.…”
Section: Production Potentialmentioning
confidence: 99%
“…Organic agriculture is an issue that is repeatedly discussed internationally (Kwasek and Obiedzińska, 2014;Kirchman and Bergström, 2008;Domagała-Świątkiewicz, 2005;Głodowska and Gałązka, 2018;Obiedzińska, 2013;Małżewska, 2015;Golik and Żmija, 2017;Runowski, 1996;Ciepielewska, 2014;Tyburski, 2013;Cupiał, Klimas, Szeląg-Sikora, Niemiec, and Sikora, 2013). In Poland (Kwasek and Obiedzińska, 2014) indicated that when comparing the production results of certified organic farms with the results of average conventional farms of the same types keeping agricultural accounts, it was noticed that organic farms obtain values at the level of about 33% of the results obtained by all the FADN farms.…”
Section: (367) 2021mentioning
confidence: 99%
“…The ecological sector of Polish agriculture is apparently strong, as Poland is third in the EU in terms of the number of ecological farms (Barłowska et al 2017). However, the problem of this sector lies in high prices for certified products, unaffordable for most Polish consumers, while 80 per cent of Polish ecological produce is exported (Golik and Żmija 2017). Moreover, ecological farms concentrate on plant production, which makes them less independent than traditional peasant farms, as those may use their own animal resources to keep the soil in good condition with natural fertilisers (e.g., with manure; see Musiał 2007;van der Ploeg 2008).…”
Section: The Context: the Silent Decline Of Smallholder Farming In Pomentioning
confidence: 99%
“…Udział produkcji i przetwórstwa ekologicznego wybranych artykułów rolno-spożywczych w produkcji i przetwórstwie ogółem według województw w 2016 roku Rysunek 3. Udział w kwotach wypłaconych dla gospodarstw prowadzących produkcję metodami ekologicznymi w poszczególnych wariantach w ramach pakietu rolnictwo ekologiczne w PROW, stan na rok 2016, dane w % Kowalska, 2015;Zuba-Ciszewska, Zuba, 2016;Golik, Żmija, 2017). Niemniej jednak nadal brakuje ich w tym zakresie dla województwa łódzkiego.…”
Section: Rolnictwo Ekologiczne W Województwie -Wybrane Aspektyunclassified
“…analiz potencjału, tendencji i uwarunkowań rozwoju) staje się popularnym przedmiotem badań naukowych (np. Wójcik, 2012;Jończyk, 2014;Kowalska, 2015;Zuba-Ciszewska, Zuba, 2016;Golik, Żmija, 2017). Niemniej jednak nadal brakuje ich w tym zakresie dla województwa łódzkiego.…”
Section: Materiał I Metodyka Badańunclassified